2017
DOI: 10.1016/j.jogn.2016.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of European Geneticists Regarding Expanded Carrier Screening

Abstract: Although a limited ECS offer is practical, it also raises concerns over equality in access to screening. A comprehensive risk-benefit analysis is needed to determine the desirability of systematic population-wide ECS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(75 citation statements)
references
References 40 publications
0
75
0
Order By: Relevance
“…8,17 They also found that physicians and genetic counselors have favorable views about the benefit of carrier screening for an expanded number of conditions. 8,[17][18][19] Of the few studies that have sought to identify which factors influence the opinions of patients on ECS and their decision to proceed with ECS when offered, an online survey by Plantinga and colleagues 12 in the Netherlands indicated that a third of responders, men or women aged 18 to 40 years and living with a partner, would elect to have ECS performed if it were offered and that they would prefer such testing to be offered by their general practitioner.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…8,17 They also found that physicians and genetic counselors have favorable views about the benefit of carrier screening for an expanded number of conditions. 8,[17][18][19] Of the few studies that have sought to identify which factors influence the opinions of patients on ECS and their decision to proceed with ECS when offered, an online survey by Plantinga and colleagues 12 in the Netherlands indicated that a third of responders, men or women aged 18 to 40 years and living with a partner, would elect to have ECS performed if it were offered and that they would prefer such testing to be offered by their general practitioner.…”
Section: Introductionmentioning
confidence: 91%
“…Despite the continued use and advancement of ECS, few studies have looked at patient attitudes towards its use, and even fewer have sought to identify patient factors or characteristics that may influence their decision to undergo ECS versus other more conventional screening options. In contrast, several studies have identified physician and other health care professional attitudes towards ECS . Collectively, these studies identified a wide variability in knowledge about basic genetics and carrier screening concepts and integration of ECS in clinical practice .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The debate as to whether to include WGS in NBS is currently taking place in many jurisdictions ( 3 5 ). There are, however, considerable concerns among health-care practitioners, including limited benefit of WGS for most healthy people in the general population, lack of expertise among non-genetic health-care providers, potential negative implications for society and scarce economic resources ( 6 8 ). It is clear that there is a gap between what is technically possible and the clinical services available.…”
Section: Introductionmentioning
confidence: 99%
“…Informed consent was obtained from all participants included in the study. The questions addressed in this paper were part of a study exploring ECS more broadly, including recommendations for the composition of ECS panels and the desirability of population-wide ECS [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%